Prevalence of Listeria monocytogenes in Human in Dhamar Governorate/ Yemen - Almashhadany, Dhary Alewy; Shater, Abdul- Rahman; Ba-Salamah, Haifa’a Abdulilah; Abd Algalil, Fahd Mohammed (Journal of medical and pharmaceutical sciences, 2018)
This research was conducted to investigate the existence and spread of Listeria monocrtogenes among different ages of human. Three hundred and ten samples (310) were collected (100 male blood, 110 female blood, and 100 Placenta). The results revealed that the overall prevalence of L. monocytogenes in total samples was N 61 (19.7%), the isolation percentage from the Female blood N 22 (20.0%) was higher than from the Male blood N 18 (18.0%), while the isolation percentage from the placenta reached to N 21 (21.0%).When we study the isolation rate of L. monocytogenes from Male blood according to Directorates , the results showed that the high rate of isolation were N 11 (31.4%) in Thamar Directorate, following Gahran N 2 (15.4%), next Ans N3 (10.7%), then Alhada N2 (9.1%), but there is no sample was isolate in Anes Directorate. Whereas the rate of isolation in Female blood according to Directorate were N 10 (29.4%) in Thamar , following N 2 (20.0%) in Anes , N 5 (17.9%) in Alhada, N 2 (14.3%) in Gahran , and N 3 (12.5%) in Ans Directorate . The highest isolation rate of the bacteria agents from placenta were in Gahran N4 (36.4%), then N9 (33.3%) in Alhada, N5 (26.3%) in Ans, N1 (16.7%) in Anes, and finally Thamar Directorate N 2 (5.4%). The results indicated that there are significant differences at (p
Keywords: Listeria monocytogenes; Human; Dhamar Governorate; Yemen